Valuation of cattle attributes in the Malian humid and sub-humid zones and implications for sustainable management of endemic ruminant livestock - Fadiga, M.L. (2013)
The preservation for future use of endemic ruminant livestock (ERL) depends on how these breeds are perceived by smallholders in relation to their Sahelian counterparts with a larger frame. These indigenous livestock breeds have unique genetic traits that are important to smallholders’ livelihood. In Mali, the dwindling number of purebred Ndama cattle, a breed known for its tolerance to trypanosomosis, is cause for concern to many stakeholders. Markets are the institutions through which the appropriate incentives to rear endemic ruminant livestock are identified. A revealed preference approach was conceptualized and applied to data collected on observed transactions in randomly selected cattle markets in the Malian humid and sub-humid zones. The results indicate that the body condition, the agroecological origin, and the category of the transacted animal are the three most important attributes. The importance of Body Condition illustrated by the high premium rates paid for excellent body condition combined with the relatively low discount rates for the Ndama and Crossbred breed confirms that if all maintenance costs are accounted for, Ndama cattle with excellent body condition could be as profitable as Zebu. The findings have production, marketing, and animal genetic resource management implications. The results would enable Ndama producers and traders to make more informed production and marketing decisions because they would be better informed about how the attributes of cattle they put on the market are rewarded or penalized. More importantly, while crossbreeding may lead to higher prices, selection within the breed and fattening are the best avenues that could lead to better prospects for Ndama producers. They lead to better prices while protecting the breed for future use.